Adoption of QRIS payment system on the intensity of interest in use on micro, small and medium enterprises - Dedy Rahman; Perengki Susanto (Universitas Negeri Padang, 2022)
This study aims to determine the effect of knowledge, perceived usefulness, perceived of ease of use, perceived of risk on the intensity of interest in using QRIS on micro, small and medium enterprises in the city of Padang. this research is quantitative. The sample used in this study was 100 samples with the criteria that MSMEs have used QRIS for at least 1 month in the city of Padang, and the method in selecting the sample is non-probability sampling. The results of this study are: that knowledge, perception of benefits, perception of ease and perception of risk all have a positive and significant effect on the intensity of interest in using QRIS on Micro, Small and Medium Enterprises in Padang City.